Interplanetary internet governance - Laura DeNardis (Centre for International Governance Innovation (CIGI), 2023)
The internet has spread to most parts of the world and is now making the leap into space. An interplanetary or solar-system internet will require a governance system that can manage the economic, political and social issues that may arise. To address these issues, internet governance will need multi-stakeholder participation from traditional governments, international organizations and the private sector. This paper looks at the challenges facing the development of a space-based internet architecture and how existing UN space governance treaties and terrestrial internet governance could help mitigate these risks.
Keywords: 330